THE IMPORTANCE OF VIDEO ANALYSIS IN HUNGARIAN FOOTBALL - TÓTH Jr., János; JÁVORCSÍK, Gabriel; TÓTH, János (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
In results-oriented football, teams use innovative technologies to increase efficiency. One of these technologies is video analytics, and we explore its importance in Hungarian football. Our research hypotheses are based on assumptions, based on which we interviewed video analysts of NB1 teams who were given a questionnaire with different questions to answer and based on their answers we evaluated their opinion on video analytics, what advantages and disadvantages could be derived from the use of video analytics. Also, how many video analysts per team are employed by an NB1 team and to what extent video analysts cooperate with scouts to help them identify talent? In our research, 20 NB1 video analysts have completed the questionnaire so far. Statistical calculations were calculated using a one-sample Wilcoxon test and a binomial test. The video analysts’ answers showed that video analysis is actively used to analyze the opponent’s game. Furthermore, video analysis is also used to analyze player performance, to develop training plans and to select new players. All in all, it can be clearly concluded that the use of video analysis has more advantages than disadvantages and that video analysis plays a positive role in Hungarian NB1 football. Received 2023 January 18; Revised 2023 June 15; Accepted 2023 June 16; Available online 2023 July 30; Available print 2023 August 30.